PENGGUNA BAHASA TERHADAP MEDIA BERITA “BABI NGEPET” (KOMPAS TV) - Eqi Safitri (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to describe how the identity and role of an ustadz in the news "Babi Ngepet" Kompas Tv. This research method uses a qualitative descriptive method. Data collection is done by means of observation. After the data is collected, it is analyzed based on the steps used, namely by clarifying the data according to the problems discussed. After that it will be concluded based on the results of the data analysis. There are several factors that influence language, one of which is identity. And as a result of this research, we find out how language influences society, and what are the roles of clerics in society, and can also reveal what actually happened in the Kompas TV news. Keywords: Language, news, sociolinguistics